2017
DOI: 10.1101/136234
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

microRNA-451a regulates colorectal cancer radiosensitivity

Abstract: 2Colorectal cancer (CRC) is a leading cause of cancer-related death. The responses of CRC to standard of care adjuvant therapies such as radiation or chemotherapy are poorly understood. MicroRNAs (miRs) are small non-coding RNAs that affect gene expression programs in cells by downregulating specific mRNAs. In this study, we discovered a set of microRNAs upregulated rapidly in response to a single 2 Gy dose fraction of γ-radiation in a mouse colorectal carcinoma xenograft model. The most upregulated candidate … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…1). Prior data demonstrated significant influence of miR-451a in colorectal cancer in vitro and in vivo models 24 (see Supplementary Figures 1, 2, 3, http://links.lww.com/SLA/B286) miR-451a was validated in our cohort out of the four upregulated mIRs shown above. Exploration of posttreatment tissue was completed, using qPCR.…”
Section: Resultssupporting
confidence: 60%
See 3 more Smart Citations
“…1). Prior data demonstrated significant influence of miR-451a in colorectal cancer in vitro and in vivo models 24 (see Supplementary Figures 1, 2, 3, http://links.lww.com/SLA/B286) miR-451a was validated in our cohort out of the four upregulated mIRs shown above. Exploration of posttreatment tissue was completed, using qPCR.…”
Section: Resultssupporting
confidence: 60%
“…22 Patients with increased CAB39 and EMSY are shown to have upregulated in a number of signaling pathways, including RAF kinases and SHP2 enzymes. 22 We have demonstrated miR-451a directly binds and downregulates CAB39 and EMSY 24 (see Supplementary Figure 4, http:// links.lww.com/SLA/B286). We inhibited RAF and SHP2 in HCT-116 cells reversetransfected with anti-miR451a.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…In addition, miR-451 is related to the inhibition of human CRC Cells via the downregulation of the Pi3k/Akt pathway [34]. Interestingly, it has been found that miR-451a affects the radiation sensitivity of colorectal carcinomas [35]. Taken together, these findings indicate that miR-451 could play a role in the development and progression of CRC, therefore, it could be a novel biomarker associated with CRC.…”
Section: Discussionmentioning
confidence: 94%